Kadar dan Daya Luteolitik PGF2? Produksi Sel Monolayer Vesikula Seminalis dan Endometrium Sapi Bali (PROSTAGLANDIN F2? CONCENTRATIONS OF BALI CATTLE ENDOMETRIAL AND SEMINAL VESICLE MONOLAYER CELLS CULTURE PRODUCTS AND ITS IN VITRO TEST ON LUTEAL MONOLAYER - Pemayun, Tjok Gde Oka; Trilaksana, I Gusti Ngurah Bagus; Mahaputra, Laba (Jurnal Veteriner; Vol 12 No 1 (2011), 2012)
The aims of this research were to determine PGF2? concentration the produced by bali cattlesendometrial and seminal vesicle monolayer cell culture and in vitro luteolytic ability on luteal monolayercell culture. The endometrial and seminal vesicle epithelial cell of bali cattle were cultured in tissueculture medium (TCM) 199 growth medium supplemented with 10% fetal calf serum and 10% EstrusMare Serum. The cells were cultured at 1.9 x 106 density per ml medium. Then Followed by incubation at38.50 C in 5% CO2 atmosphere for 12 days. The level of PGF2? in the cell culture medium were assayed byRadioimmnuassay (RIA) technique. The luteal cells were cultured in 9 days incubation and divided into 2groups. Group I were added with 10% of cell culture product and group II were added with 1,25 mgdinoprost/ml. The level of progesterone produced by luteal cell culture was measured at day 9th and 11thincubation. The result showed concentration of PGF2? cell product of seminal vesicle cell culture wassignificantly higher (P < 0.05) compared to endometrial cell culture. There was no significant difference(P>0.05) in luteolytic ability between PGF2? cell culture product and dinoprost. In conclusion, the PGF2?could be produced by monolayer cell culture of bali cattle is endometrial and seminal vesicle epithelialcells more over they have similar ability with dinoprost in luteolytic ability.
Keywords: PGF2?, Seminal Vesicle, Endometrial cell, Progesterone